Aktualisasi Nilai-Nilai Tasawuf dalam Buku Wasiat Renungan Masa Karya TGKH. Muhammad Zinuddin Abdul Madjid di Madrsah Aliyah Mu’alimin NW Anjani - Gani, Abdul; Fahururrozi, Fahururrozi; Thohri, Muhammad (Jurnal Ilmiah Profesi Pendidikan, 2024)
Sufism, a significant aspect of Muslim life, emphasizes spiritual development and the individual's connection with God. TGKH. Muhammad Zinuddin Abdul Madjid's book "Wasiat Renungan Masa" stands as a valuable legacy, guiding individuals in exploring life's meaning and religious teachings. Despite this, research on the actualization of Sufi values from the book in an educational context remains limited. This study analyzes how these values are realized in Madrasah Aliyah Mu'alimin NW Anjani. Employing a qualitative approach with a case study design, data is gathered through interviews, classroom observations, and document analysis. The study identifies and analyzes key themes related to Sufi values in "Wasiat Renungan Masa." Results show that the actualization involves Sufi-based education, providing spiritual enlightenment and character strengthening. Methods include indoctrination, reflection, application, education, and awareness. Factors influencing actualization include supportive infrastructure, teacher understanding, and curriculum integration. Leadership, parental involvement, and community participation reinforce Sufi teachings. Conversely, constraints include facility limitations, teacher understanding, curriculum depth, financial constraints, and low student participation.